2020
DOI: 10.1093/nar/gkaa564
|View full text |Cite
|
Sign up to set email alerts
|

CASC3 promotes transcriptome-wide activation of nonsense-mediated decay by the exon junction complex

Abstract: Abstract The exon junction complex (EJC) is an essential constituent and regulator of spliced messenger ribonucleoprotein particles (mRNPs) in metazoans. As a core component of the EJC, CASC3 was described to be pivotal for EJC-dependent nuclear and cytoplasmic processes. However, recent evidence suggests that CASC3 functions differently from other EJC core proteins. Here, we have established human CASC3 knockout cell lines to elucidate the cellular role of CASC3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 97 publications
7
32
0
Order By: Relevance
“…Only when we deplete in UPF3A or UPF3B KO cell lines the respective other protein by RNAi or genomic KO, NMD efficiency substantially decreases. It should be noted that the effects of a KO on NMD activity are typically stronger than those of a KD, which is consistent with our earlier observations (Boehm et al, 2021;Gerbracht et al, 2020 (Yi et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Only when we deplete in UPF3A or UPF3B KO cell lines the respective other protein by RNAi or genomic KO, NMD efficiency substantially decreases. It should be noted that the effects of a KO on NMD activity are typically stronger than those of a KD, which is consistent with our earlier observations (Boehm et al, 2021;Gerbracht et al, 2020 (Yi et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Mass spectrometry of RNPS1 and CASC3 containing EJCs showed that CASC3 but not RNPS1 preferentially associates with UPF3B (Mabin et al, 2018). Consistent with this observation, a recent report found a much-reduced EJC-UPF3B association in CASC3 knockout HEK293 cells (Gerbracht et al, 2020). Together, these observations suggest a link between EJC composition and UPF3B-mediated NMD.…”
Section: Introductionsupporting
confidence: 75%
“…We next tested the contribution of other factors from the EJC-mediated NMD pathway to UPF3 function in this branch of NMD. We first focused on CASC3-containing EJC as previous observations from human embryonic kidney (HEK293) cells suggest that there exists a functional synergy between the CASC3-containing EJC and UPF3B (Gerbracht et al, 2020; Mabin et al, 2018). To test if CASC3-UPF3B preferential association is also present in other cell types, we overexpressed in HeLa cells either wild-type CASC3 or a mutant CASC3 (HDAA) that is unable to associate with the EJC core (Ballut et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…A fourth core subunit, known as Barentsz (Btz), Cancer susceptibility candidate gene 3 (CASC3), or Metastatic lymph node 51 (MLN51), associates with the complex following the completion of splicing, and is required for the effects of the EJC on translation, NMD and mRNA localization (Chazal et al, 2013; Palacios et al, 2004; Shibuya et al, 2006; van Eeden et al, 2001). The transition between RNPS1 and CASC3-containing forms of the EJC alters the set of transcripts subject to NMD, although distinct effects have been reported in two studies (Gerbracht et al, 2020; Mabin et al, 2018). In the mouse brain, haploinsufficiency for Magoh, Rbm8a or Eif4a3 causes severe microcephaly, but complete loss of Casc3 has a much milder effect that can be attributed to developmental delay (Mao et al, 2017; Mao et al, 2016; Mao et al, 2015; Silver et al, 2010).…”
Section: Introductionmentioning
confidence: 94%